Electricity and electronics for HVAC - Miller, Rex 1929- (McGraw Hill, 2007)
Electricity and Electronics for HVAC provides an expert account of the electric and electronic components used for modern air conditioning, heating, and refrigeration systems. Packed with hundreds of detailed illustrations, this in-depth reference fully explains circuits, diagrams, digital controls, safety procedures, troubleshooting, and more.